Induction of p53 in keratinocyte cultures treated with Behçet's patient sera. (1st March 2020) - Houacine, Sihem; Kang, Angray; Parkinson, Eric Kenneth; Wan, Hong; Fortune, Farida
Abstract: Background: Behçet's disease (BD) is a rare, multisystem vasculitis disease characterized by recurrent orogenital ulcerations with its etiology remained unclear. The transcription factor p53 has been reported to be upregulated in some autoimmune diseases, such as lupus erythematosus, dermatomyositis, and psoriasis. However, little is known about its alteration in BD. Methods: Keratinocyte cultures of both skin and oral origins were treated sera of 18 Behcet patients for 24 hours and analyzed by indirect immunofluorescence for p53 expression. The specificity of p53 expression was confirmed by siRNA‐mediated p53 knockdown and the serum IgG removal studies. The expression of p53 levels was quantitatively analyzed with ImageJ. Results: It was shown that the expression of p53 is increased in skin and oral keratinocyte cell lines, in both the nucleus and cytoplasm of cells treated with patient sera compared to controls. Either p53 knockdown or IgG removal results in a reduction of p53 levels relative to cells treated with patient sera without p53 knockdown or IgG depletion. Conclusions: This in vitro study provides the first evidence that BD sera can induce the p53 expression in keratinocytes that may have implications in Behcet pathogenesis.